Revenue Diversification and Reform in Ethiopian Higher Education - Mengistu Feleke, Kibrome (International Higher Education, 2016)
The higher education system in Ethiopia has been undergoing rapid transformation and massive expansion over the last two decades that increases the number of universities and enrolments. However, state funding has been unable to keep pace with the continuously expanding system. Hence, the current expansion has created serious financial pressures. Given the limited public funding and the hugely expanding system, therefore, the move towards increased search for non-governmental sources of revenues has become among the forefront agenda in Ethiopian higher education system.